Analisis Kesiapan Masyarakat Pada Penerapan Smart City di Sosial Media Menggunakan SNA - M. Khairul Anam; Tri Putri Lestari; Latifah; Muhammad Bambang Firdaus; Sofiansyah Fadli (Ikatan Ahli Informatika Indonesia (IAII), 2021)
Smart People, which means smart city residents or people, not only refers to one's education but also the quality of social interactions that are formed. This Social Network Analysis (SNA) emphasizes the relationship between actors / users rather than the attributes of these actors. This analysis aims to see whether the people of Pekanbaru are ready to face changes to a Smart City. Pekanbaru is a civil city that will build a Smart City, with a concept that adopts 6 pillars, one of which is Smart People. There are 720,000 Twitter users in Pekanbaru City, while the people who actively interact are only 227 users or around 0.031%. Meanwhile, a city that can be said to be ready should be around 60-80% of active users who provide opinions or comments to the government of Pekanbaru City. From this research, it can be concluded that the people of Pekanbaru City are not ready to face Smart City Madani as seen from the interaction of the community on social media Twitter.